2004
DOI: 10.1002/bjs.4545
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation for faecal incontinence in the UK

Abstract: SNS is a safe and effective treatment, in the medium to long term, for faecal incontinence when conservative treatment has failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
3
17

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(148 citation statements)
references
References 27 publications
7
121
3
17
Order By: Relevance
“…9 Further studies have shown similar improvement. 10,11 In a similar manner, it was observed in some of our incontinence patients there was a subjective effect on defecation. Evidence for a possible role in constipation arose initially from urological patients.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…9 Further studies have shown similar improvement. 10,11 In a similar manner, it was observed in some of our incontinence patients there was a subjective effect on defecation. Evidence for a possible role in constipation arose initially from urological patients.…”
supporting
confidence: 80%
“…Subsequent reports have confirmed this clinical benefit and have emphasised the safety of this procedure. 10,11 NICE guidelines have been issued for 2005 confirming the safety and efficacy of sacral nerve stimulation for faecal incontinence, leading the way for SNS to be performed as a main-stream treatment when conservative treatment fails, rather than restricted to the research arena alone.…”
Section: Discussionmentioning
confidence: 99%
“…Tibial nerve stimulation was first used in urology to treat urge-incontinence and overactive bladder syndrome [14,15]. The exact mechanism of PTNS is unknown but some studies showed, as the current study, an increase in maximal squeeze pressure suggesting facilitation of striated muscle function [16]. Increased rectal sensitivity to balloon distention suggests that peripheral neuromodulation affects afferent sensory nerves.…”
Section: Discussionmentioning
confidence: 55%
“…Si se observa una disminución de al menos el 50% de los episodios de incontinencia, se implanta un sistema de estimulación defi nitiva 35 . Esta técnica ha mostrado ser exitosa en la mayoría de las series (70-95%) con una media de seguimiento de un año (35)(36)(37)(38)(39), con baja morbilidad (infección 3-7%) 39 y asociada a mejoría en la calidad de vida. El tratamiento con estimulación de los nervios sacros debe restringirse a pacientes con esfínter anal externo intacto.…”
Section: Neuromodulación Sacraunclassified